THE IMPACT OF CORPORATE GOVERNANCE MECHANISMS ON EARNING MANAGEMENT PRACTICES IN LIGHT OF THE COVID19 PANDEMIC USING THE ARDL MODEL - AN APPLIED STUDY ON IRAQI COMPANIES (World Economics and Finance Bulletin, 2023)
This study aims to determine the impact of corporate governance mechanisms represented by the factors of board size, ownership focus and company size on earning management, taking into consideration the COVID19 period as an independent variable in a number of 13 Iraqi companies for a period of time represented by 2017-2021, represented by the problem of the study with: What is the impact of corporate governance mechanisms on earning management practices in light of covid-19? The study used the method of analyzing integrated time series regression models using (ARDL) Auto-Regressive Distributed Lag Model, and the study data was processed using the E-views12 program, The study found that the Board of Directors (BSIZE) and the coronavirus pandemic COVID-19 have a unilateral impact on earning management (EM), while the coefficient of ownership concentration, company size and company indebtedness indicate an adverse impact on earning management (EM), but this effect is not morally significant at a 5% indicative level.
Keywords: Corporate governance; earning management